2017
DOI: 10.3945/cdn.117.001396
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Dietary Patterns on Plasma Soluble CD14, a Surrogate Marker of Gut Barrier Dysfunction

Abstract: Background Specific foods and nutrients, including alcohol, may contribute to gut barrier dysfunction. However, to our knowledge, the influence of whole diets is currently unknown. Objective We aimed to cross-sectionally investigate associations of dietary patterns with plasma soluble CD14 (sCD14), which is released by macrophages on stimulation with endotoxin and has been used as a marker of gut hyperpermeability. Methods We used food-frequency questionnaire data collected from 689 women in the Nurses’ He… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 54 publications
1
17
0
Order By: Relevance
“…Suthat Liangpunsakul, et al in 2017 describe how there is a positive correlation between alcohol consumption and the increase in sCD14 levels. This is even more observed when combined with alcohol consumption there is a high intake of red and processed meats, high-fat dairy products (e.g., whole milk and cream), refined grains, and desserts [47]. Zuleika Michelini, et al in 2016, presented a similar result.…”
Section: Discussionmentioning
confidence: 89%
“…Suthat Liangpunsakul, et al in 2017 describe how there is a positive correlation between alcohol consumption and the increase in sCD14 levels. This is even more observed when combined with alcohol consumption there is a high intake of red and processed meats, high-fat dairy products (e.g., whole milk and cream), refined grains, and desserts [47]. Zuleika Michelini, et al in 2016, presented a similar result.…”
Section: Discussionmentioning
confidence: 89%
“…We found that sCD14 levels were increased in SLE, confirming previous studies (23, 54, 55). Recent reports demonstrated that elevated levels of sCD14 in plasma are associated with intestinal barrier dysfunction (56, 57). The positive correlation between sCD14 and disease activity (SELENA-SLEDAI score) levels suggests a role for endotoxemia in SLE progression.…”
Section: Discussionmentioning
confidence: 99%
“…However, none of these approaches is without pitfalls. For example, circulating LPS and zonulin levels are not considered reliable markers for compromised gut permeability due to technical difficulties in quantification (57, 100103). The acquisition of intestinal tissue from SLE patients and controls is uncommon, which makes such an approach less feasible.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Elevated levels of sCD14 could be caused by bacterial exposure, alterations in the microbiome, compromised gut integrity and increased levels of cytokines. This would induce monocyte/macrophage activation and elevate the circulating concentrations of sCD14 (43,(81)(82)(83)(84)(85)(86). Release of sCD14 by synovial macrophages was also suggested to contribute to elevated levels in RA patients (74).…”
Section: Discussionmentioning
confidence: 99%